The Effect of Various Testing Conditions on Long-Term Retention of Reading Materials: The Case of Initial and Delayed Test Types, and Feedback on Test - Mahmoud Qaracholloo; Mohammad Reza Ghorbani; Farhad Ghiasvand (Journal of Modern Research in English Language Studies)
This study investigated various testing conditions for their influence on long-term retention of reading materials. To do so, 84 English as Foreign Language (EFL) learners were randomly selected from a total of 746 and were randomly divided into two equal groups to participate in two experiments. In each experiment, the participants studied some texts and participated in some initial testing conditions before taking a 10-day delayed final exam. The testing conditions of the first experiment were 1) study + simultaneous open-book test, 2) study + open-book test, 3) study + closed-book test + feedback, 4) study + closed-book test, 5) no study no test, and 6) study with no test. The second phase was a replication of the first 5 testing conditions of the first phase accompanied by 3 more conditions, namely, 6) study + study, 7) study + study + study, 8) study + study + study + study. Analysis of variance results showed that different test types, feedback on test, and restudying could differently influence long-term retention. It was found that feedback on test had the highest effect on retention. Similarly, taking a test after study was more influential than restudying. Finally, open-book testing worked better than closed-book testing.